Moral Rights Protection of Music Creators' Reputation Under the Berne Convention 1886 - Putri Khalisha Humaira Yusuf; Christine S.T Kansil, S.H., M.H (Dinasti Research, 2024)
Berne Convention for the Protection of Literary and Artistic Works 1886 is one of the main pioneers regarding the protection of works as copyright internationally. The establishment of the agreement is intended to provide standardization for each state party internationally as an effort to protect every work in the world. One of the protection efforts is through moral rights attached to the creator or owner of the work who has the right of attribution to take ownership claims to a work and the right of integrity to prevent his work from being misused which can have an impact on his honor or reputation. Moral rights violations, especially in musical works, often occur in the world even though the economic rights have been transferred and also during major events such as presidential candidate campaigns. However, the application of law enforcement and sanctions provided by this agreement to perpetrators of moral rights violations are regulated in the domestic law of each state party through the harmonization of these regulations. The research method used is a normative juridical approach.